Competences of Heads of Schools in the Current Terminology of Education in Latvia - Driksna, Mārtiņš; Kaļķe, Baiba (Acta Paedagogica Vilnensia, 2022)
This study examined competences of heads of schools when acquiring the current terminology of education in Latvia. In the school year 2020/2021 schools in Latvia implemented new approach to learning by introducing the curriculum reform called “Introducing the competence approach in the instructional content “Skola 2030”. The event led to several changes in the curriculum as well as an addition of various new terms to be used when introducing the reform to schools; therefore, to successfully implement the reform heads of schools have to fully understand the new curriculum and terms. The aim of this research paper was to study what the necessary competences of heads of schools are when acquiring the current terminology of education. To achieve the objective, analysis of theoretical literature, scientific research and statistics were performed; a survey for heads of schools was developed and conducted; the results of the study were compiled. In the empirical part it was clarified which were the necessary competences of heads of schools that related to acquiring, using, and passing on the terminology of education. The study found that in the acquisition of the current education terminology the most important competences are social competence, methodological competence, self-competence and their subcompetences.